2010
DOI: 10.3233/jad-2010-1229
|View full text |Cite
|
Sign up to set email alerts
|

Complex Antioxidant Blend Improves Memory in Community-Dwelling Seniors

Abstract: Abstract.One hundred thirteen community dwelling subjects between the ages of 50 and 75 without dementia were recruited. A blind administrator randomly assigned 54 subjects to placebo and 59 to active treatment groups. The active treatment consisted of four months treatment with a complex antioxidant blend. Placebo treatment was an identical gel and bottle administered for four months. Forty-eight active subjects and 38 placebo subjects completed the study. Memory testing with a 50 part paired association test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…There were no benefits to aspects of mood including depression or ratings of physical and mental fatigue. In contrast to chronic studies in older people, which have shown improvements to memory (Harris et al 2012;Summers et al 2010), a single MVMH dose did not exert any effects on cognitive performance.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…There were no benefits to aspects of mood including depression or ratings of physical and mental fatigue. In contrast to chronic studies in older people, which have shown improvements to memory (Harris et al 2012;Summers et al 2010), a single MVMH dose did not exert any effects on cognitive performance.…”
Section: Discussionmentioning
confidence: 43%
“…Randomised controlled trials have demonstrated that supplementation with multivitamins containing minerals and herbs, over a period of 2 to 4 months, can enhance various domains of memory in those over the age of 50 (Harris et al 2012;Summers et al 2010). In men aged 50-69 years, 8-weeks multivitamin/mineral and herbal (MVMH) supplementation has been shown to reduce symptoms of mood disorder, problems with day-to-day functioning and increase positive mood experience (Harris et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the cognitive improvements identified by Summers et al (2010) were promising, without the examination of treatment effects on other biological indices such as blood measures of vitamin status, oxidative stress, inflammation or cardiovascular parameters, the mechanisms of action can only be speculated. Whilst a 3-year trial designed to reduce homocysteine through folate supplementation demonstrated improvements to memory, as assessed by a verbal learning task, information processing speed and sensorimotor speed in seniors aged 50-70 years (Durga et al 2007), there is little evidence that in healthy elderly, lowering homocysteine, through shorter term B vitamin supplementation alone, improves cognition (Lewerin et al 2005;Eussen et al 2006;McMahon et al 2006;Balk et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Other plant extracts containing flavonoid components have also been suggested to improve cognition (Macready et al 2009). Positive results regarding herbals combined with vitamins has been obtained from a recent 4-month trial in elderly subjects which examined the effects of a complex antioxidant blend consisting of vitamins, minerals, amino acids, lipids and herbal extracts, all with antioxidant properties (Summers et al 2010). Herbal components of this formula included flavonoids, Ginkgo biloba, grape seed and gotu kola-ingredients which have gained interest as potential modulators of cognitive function (Macready et al 2009;Spencer 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Four-month administration of complex antioxidant blend (34 components including antioxidant vitamins, microelements, ginseng, grape seed extract, gotu kola, ginkgo biloba) reduced circulating homocysteine along with improvement of memory function in community-dwelling seniors without dementia at baseline (Summers et al 2010 ).…”
Section: Interventional Studies: Results Of Randomized Double-blindmentioning
confidence: 99%